2013
DOI: 10.1128/jvi.02122-12
|View full text |Cite
|
Sign up to set email alerts
|

Significant Reductions in Gag-Protease-Mediated HIV-1 Replication Capacity during the Course of the Epidemic in Japan

Abstract: f Human immunodeficiency virus type 1 (HIV-1) evolves rapidly in response to host immune selection pressures. As a result, the functional properties of HIV-1 isolates from earlier in the epidemic may differ from those of isolates from later stages. However, few studies have investigated alterations in viral replication capacity (RC) over the epidemic. In the present study, we compare Gag-Protease-associated RC between early and late isolates in Japan (1994 to 2009). HIV-1 subtype B sequences from 156 antiretro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 95 publications
(117 reference statements)
1
16
0
Order By: Relevance
“…As described above, transmission of viruses with high replication capacity tends to result in more rapid CD4 decline in the recipient (8) and hence HIV-infected people with low CD4 counts tend to have viruses with high replicative capacity, as observed in this study and several others (14,(17)(18)(19)(20). To examine the plausibility of this hypothesis, we developed a mathematical model, first, to investigate how HIV virulence would be expected to change over the course of the epidemic in the absence of ART; and, second, to examine the anticipated impact that ART would have on virulence (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…As described above, transmission of viruses with high replication capacity tends to result in more rapid CD4 decline in the recipient (8) and hence HIV-infected people with low CD4 counts tend to have viruses with high replicative capacity, as observed in this study and several others (14,(17)(18)(19)(20). To examine the plausibility of this hypothesis, we developed a mathematical model, first, to investigate how HIV virulence would be expected to change over the course of the epidemic in the absence of ART; and, second, to examine the anticipated impact that ART would have on virulence (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, the true VRC of HIV in each study subject is only partially represented by the assay, and also it is possible that mutations outside of GagProtease may compensate for mutants within Gag-Protease and vice versa. However, the assay has been adopted and validated by several groups, including the demonstration of a correlation between the replication capacities of Gag-recombinant viruses and complete HIV isolates obtained from the same patient samples (31); and, consistently in these studies, the measured VRC correlates with viral set point and, inversely, with CD4 count (14,(17)(18)(19)(20), suggesting that the gag-pro sequence has an important influence on HIV disease outcome, independent of the effects of other genes on VRC. In addition, the CTLs that have been most clearly related to immune control and that dominate the HIV-specific response in subjects expressing the protective HLA alleles HLA-B*57/58:01/27/81:01 are within Gag (9,44), and the escape mutants within these Gag epitopes have been proposed to play a critical role in immune control via a reduction on VRC (9-12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in Japan, where the frequency of B*51 exceeds 20%, the frequency of RT I135X exceeds 70%, supporting the spread of the polymorphism at the population level in the country. Studies in Europe (30), Asia (31), and Africa (32) have also reported (or inferred) decreases in HIV-1 replication capacity over the course of their respective epidemics, presumably as a result of HIV-1 adaptation to host pressures. A recent study of HIV-1 Gag and Nef evolution in North America by our group also indicated that HLA-associated polymorphisms have spread in circulation over time (33).…”
Section: H Uman Leukocyte Antigen (Hla) Class I-restricted Cd8mentioning
confidence: 99%